Asset Management for Part of Nablus City Road Network & Design for Tell-Nablus Al-Jadeda Road - Ola Aqqad; Nadeen Khalaf; Heba Aghbar; Walaa' Khalili – (My University, 2019)
It is known that Palestinian cities suffer from deterioration in infrastructure facilities. The City of Nablus is one of those cities which suffers from problems in asphalt pavement networks. Asphalt is a flexible pavement that is used for parking lot, roads, driveways and other surfaces. The flexibility of asphalt allows it to expand. The troubles in pavement started to appear since the roads network have been constructed in the city. The case study includes four main roads in the city with a total length of about 4000m. These roads are selected in coordination with Nablus Municipality, including Hamdi Kanan, Amman, Malhees and Al-Makhfiya Streets with a length of,500,1200,1300 and 1000m, respectively. The roads were divided into sections of 100m length. Pavement Condition Index (PCI) was calculated to rate the condition of each section. The objective of the project is to use asset management by setting standards for priority maintenance activities for the targeted roads with the using of priority indicator which explains the condition of the pavement in addition to other criteria such as functional classification of roads, traffic volume and safety, etc. Moreover, it takes also the condition of other utilities in the streets, such as water,sewage,telecommunications and electricity networks. As mentioned earlier, Pavement Condition Index (PCI) indicator is used to present the general condition of the pavement and to identify the type of maintenance to be used to produce a good pavement management system(PMS) by using computer software such as PAVER. Then a sample from each road was taken from the severe distresses areas and these samples was analyzed at the material lab of the university. Finally, the work done was presented in a report with all necessary figures, maps, and tables. Finally, as, Palestinian cities suffer from lack in funding and budgets which should be specified for maintaining the roads. A prioity index, is a part of PMS for the roads network, which is used to help the decision-makers to make the right decision and use the allowable funds in an appropriate way. Also Nablus City attends major traffic movement due to the large commercial and population activities, and because of its central location between the west Bank’s main cities . It’s considered as a link between those cities, causing traffic jams in the city center and that requires a presence of an alternative and circular streets such as (Ring road), in order to reduce the large volume of traffic and the delay. The second part of the project is the design of Tell-Nablus Al-Jadeda Road, in the southern west of the city of Nablus. The project includes the geometric design at the targeted road. Starting from An-Nour Mousque Junction and ending at Nablus AL-Jadeda Roundabout with a length of 487m , provided all needed data sheets maps. The design criteria isperformed based on AASHTO 2011 and using Civil 3D software. The design includes the preparation of Horizontal Plans, Profiles and cross sections of the road as well as intersections and pavement design.